Child Marriage in Indonesia: How Communities Navigate Marriage Practices within Islamic, Adat, and State Norms - Lena Hanifah; Tavinayati; Varinia Pura Damaiyanti; Nor Ismah (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2026)
This qualitative study, based on interviews and focus group discussions, examines how communities in South Kalimantan address child marriage within a plural legal framework. It addresses two central questions: how communities in South Kalimantan negotiate child marriage within the context of legal pluralism, and how the concept of marital readiness is constructed and understood within the legal consciousness of families, religious leaders, and community members. Using Participatory Qualitative Research, the study was conducted in two villages with distinct social characteristics: Cukan Lipai in Hulu Sungai Tengah Regency and Berangas Timur in Barito Kuala Regency. The findings reveal that communities in both villages prioritize customary norms and religious teachings, particularly Islamic law, over state law when determining the appropriate age and readiness for marriage. In many cases, religious reasoning and biological signs of maturity are used to justify child marriage, aligning with some classical fiqh interpretations that link marital eligibility to puberty. Meanwhile, formal legal provisions such as Law Number 16 of 2019 on Marriage and its dispensation mechanism are often viewed merely as administrative formalities that can be negotiated or bypassed through practices like unregistered marriages (kawin siri), which are considered religiously valid. Within this context, communities construct and obey their own norms. Therefore, efforts should bring together state law, Islamic principles, and local customary practices to narrow the gap between legal systems and how communities actually live and make decisions.